Strengthening Of Character Education Through The Method To Play Role In Early Childhood - Nurul Akmal; Nasriah Nasriah (PG PAUD FIP UNIMED, 2017)
Character education in values is very important to start in early childhood because of character education is the education process, aimed at developing values, attitudes, and behaviors that emit high moral or noble character, and 18 grains of values of character education, namely, Religious, Honest , Tolerance, Discipline, Work Hard, Creative, Independent, Democratic, curiosity, Excitement ethnicity, Love the motherland, Rewarding achievements, Friendly / communicative, Love Peace, Joy of reading, Care for the environment, social Caring, responsibility. In order for character education can be achieved, especially in early childhood, which is referred to as a golden age because at this age children easily able to absorb and imitate all that is seen, taste and hearing, then Education characters require special methods appropriate for educational purposes can be achieved. One of the learning methods suitable for early childhood is in the form of play that contains elements of habituation exemplary method is the method of playing a role that can be done with simple and does not require high costs so easy to use in the conditions and circumstances.